2014
DOI: 10.1007/s00464-014-3697-1
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy mitigates adverse oncological effects of delayed adjuvant chemotherapy for colon cancer

Abstract: The benefits of quicker recovery after laparoscopic surgery did not translate into earlier initiation of adjuvant chemotherapy in this retrospective study. However, a laparoscopic approach negated the inferior oncologic outcomes of patients who received delayed initiation of chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…There was no decrease in survival in the laparoscopic group. 2 We also found no significant differences between laparoscopic and robotic MIS approaches for time to chemotherapy and other outcomes. Our study showed time from surgery to chemotherapy more comparable to the NCD study, with about 30% of our MIS patients and about 50% of open colorectal resections starting chemotherapy >8 weeks after surgery.…”
Section: Discussionmentioning
confidence: 55%
“…There was no decrease in survival in the laparoscopic group. 2 We also found no significant differences between laparoscopic and robotic MIS approaches for time to chemotherapy and other outcomes. Our study showed time from surgery to chemotherapy more comparable to the NCD study, with about 30% of our MIS patients and about 50% of open colorectal resections starting chemotherapy >8 weeks after surgery.…”
Section: Discussionmentioning
confidence: 55%
“…Because of retrospective data collection, our study also presents a potential information bias. Moreover, we were not able to analyse some risk factors suggested in other studies such as tumour grade, 5,26,38 marital status, 5,26 socioeconomic status 26,31,39,40 and patient comorbidities 5,26,39,41–43 …”
Section: Discussionmentioning
confidence: 92%
“…Moreover, we were not able to analyse some risk factors suggested in other studies such as tumour grade, 5,26,38 marital status, 5,26 socioeconomic status 26,31,39,40 and patient comorbidities. 5,26,39,[41][42][43] Finally, we used an MFP approach which has several advantages over the current approach of categorising continuous variables, especially regarding relationship modelling, quality of fit and power. 44 Our study suggests that in addition to colectomy following an ED visit and placement of stoma, factors related to health care organisation (additional scheduled care after colectomy, extended time-to-PMM) and access to care (travel time to hospital) could be associated with a higher risk of late aCT administration after colectomy, which is…”
Section: Weaknesses and Strengths Of This Studymentioning
confidence: 99%
“…Even though we did not find a significant correlation between complications and IDRF-Status (which may be explained through a low patient number), we described a significant correlation for surgical complications and OS. Patients who suffer from complications after oncological surgery experience often a delay in further treatment with chemotherapy and/or radiation, which may lead to further tumor progression and therefore, decreased OS [1,11,19,24]. Hypothetically speaking, this might be applicable for NB as well.…”
mentioning
confidence: 99%